Providing financial and economic security for Ukrainian dairy industy enterprises - Keranchuk, Tatiana (My University, 2016)
At the current stage, Ukraine is actively cooperating with the EU. Therefore, it is important to explore the integration possibilities of Ukrainian dairy enterprises to foreign industrial markets, including the EU market. Particularly relevant issues need to protect domestic local milk producers at the state level in the process of international economic integration. У роботі розглянуті сучасні проблеми інтеграції українських підприємств молочної галузі на зовнішні галузеві ринки, в тому числі ринок ЄС. Висвітлюються проблеми необхідності захисту вітчизняних виробників молока та молочних продуктів на державному рівні в ході процесів міжнародної економічної інтеграції та особливості формування механізму фінансово-економічної безпеки підприємств молочної промисловості.
Keywords: економічна інтеграція; глобалізація; фінансово-економічна безпека; молочна галузь; якість; еconomic integration; globalization; finance and economic security; the dairy industry; the quality of dairy products; кафедра економіки і права